2015
DOI: 10.1111/iwj.12551
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐conditioned medium accelerates wound healing with fewer scars

Abstract: Mesenchymal stem cells (MSCs) derived from umbilical cords (UC-MSCs) have been shown to enhance cutaneous wound healing by means of the paracrine activity. Fibroblasts are the primary cells involved in wound repair. The paracrine effects of UC-MSCs on dermal fibroblasts have not been fully explored in vitro or in vivo. Dermal fibroblasts were treated with conditioned media from UC-MSCs (UC-MSC-CM). In this model, UC-MSC-CM increased the proliferation and migration of dermal fibroblasts. Moreover, adult dermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 42 publications
(54 reference statements)
3
89
0
1
Order By: Relevance
“…They express such antigens as CD73, CD90 and Cd105 and should not express CD14, D19, CD34, CD45, CD11b, CD79a and HLA-DR surface molecules. 3,6,9,[139][140][141][142] Bone marrow, the umbilical cord, adipose tissue, placenta and cord blood all provide sources of MSCs ( Figure 6) containing the therapeutic potential for the treatment of wound healing disorders. 143 With respect to normal cutaneous wound healing, MSCs are mobilized from their host sources to the injury site where they support skin repair despite hypoxia and a lack of nutrients.…”
Section: Mscs and Their Putative Mechanism Of Action In Wound Repairmentioning
confidence: 99%
“…They express such antigens as CD73, CD90 and Cd105 and should not express CD14, D19, CD34, CD45, CD11b, CD79a and HLA-DR surface molecules. 3,6,9,[139][140][141][142] Bone marrow, the umbilical cord, adipose tissue, placenta and cord blood all provide sources of MSCs ( Figure 6) containing the therapeutic potential for the treatment of wound healing disorders. 143 With respect to normal cutaneous wound healing, MSCs are mobilized from their host sources to the injury site where they support skin repair despite hypoxia and a lack of nutrients.…”
Section: Mscs and Their Putative Mechanism Of Action In Wound Repairmentioning
confidence: 99%
“…Wounds treated with the UC-MSC conditioned media also healed faster with decreased collagen accumulation. (Li, et al, 2015) Additionally, in vitro studies have shown that human amniotic fluid-derived MSC conditioned media has the potential to inhibit the pro-fibrotic actions of TGF-β1 and even reverse the myofibroblast phenotype to a fibroblast-like state. Conditioned media from ASCs produced similar results, but to a lesser extent.…”
Section: Recent Advances In Scarless Wound Healing Researchmentioning
confidence: 99%
“…Tang et al also reported that DPSCs had inhibitory effects on the proliferation of PBMCs [16]. Some studies reported that the conditioned-medium mesenchymal stem cells had anti-inflammatory effects [17,18]. Yamaguchi and collogues showed that DPSCs-CM could reduce cardiac injury [19].…”
Section: Discussionmentioning
confidence: 98%